2018
DOI: 10.1038/s41593-018-0072-x
|View full text |Cite|
|
Sign up to set email alerts
|

Medial preoptic circuit induces hunting-like actions to target objects and prey

Abstract: As animals forage, they must obtain useful targets by orchestrating appropriate actions that range from searching to chasing, biting and carrying. Here, we reveal that neurons positive for the α subunit of Ca/calmodulin-dependent kinase II (CaMKIIα) in the medial preoptic area (MPA) that send projections to the ventral periaqueductal gray (vPAG) mediate these target-directed actions in mice. During photostimulation of the MPA-vPAG circuit, mice vigorously engaged with 3D objects and chased moving objects. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 53 publications
1
78
0
Order By: Relevance
“…In rats, lesioning of the zona incerta impairs feeding responses 45 while, conversely, in mouse models, optogenetic stimulation of GABAergic neurons in the zona incerta leads to rapid, binge-like eating and body weight gain 46 . Activation of projections from the hypothalamic preoptic nucleus (DEINH5; POA-NEURO21, POA-NEURO66) to the ventral periaqueductal gray (MEGLU2 and MBDOP1) induce object craving 47 , whereas pharmacological inactivation of the periaqueductal gray decreases food consumption 48 . Together, these findings suggest that susceptibility to obesity is enriched in cell types processing sensory stimuli and directing actions related to feeding behavior and opportunity.…”
Section: Processing Of Sensory Stimuli and Feeding Behaviormentioning
confidence: 99%
“…In rats, lesioning of the zona incerta impairs feeding responses 45 while, conversely, in mouse models, optogenetic stimulation of GABAergic neurons in the zona incerta leads to rapid, binge-like eating and body weight gain 46 . Activation of projections from the hypothalamic preoptic nucleus (DEINH5; POA-NEURO21, POA-NEURO66) to the ventral periaqueductal gray (MEGLU2 and MBDOP1) induce object craving 47 , whereas pharmacological inactivation of the periaqueductal gray decreases food consumption 48 . Together, these findings suggest that susceptibility to obesity is enriched in cell types processing sensory stimuli and directing actions related to feeding behavior and opportunity.…”
Section: Processing Of Sensory Stimuli and Feeding Behaviormentioning
confidence: 99%
“…This opens up new directions of research studying the mouse superior colliculus to understand further aspects of approach behavior such as rapid object identification, stimulus valence assignment, target selection, behavioral choice and sustained pursuit of targets. In future work, it will be also be fruitful to further explore how the cell types accessed here contribute to other natural visually-guided behaviors in the mouse such as active predator avoidance, navigation or novel object exploration (Cooper et al, 1998;Park et al, 2018) . Importantly, it is also well established that SC, particularly in higher mammals is required for more complex visuomotor and even cognitive functions, such as spatial selective attention (for recent reviews see (Basso and May, 2017;Krauzlis et al, 2013) .…”
Section: Conserved Visually-guided Behaviors Supported By Specific Scmentioning
confidence: 99%
“…The central amygdala (CeA) displays activity changes during hunting (Comoli et al , 2005) and optogenetic activation of the CeA→ventral PAG pathway motivates prey pursuit (Han et al , 2017). Stimulation of the medial preoptic area to vPAG pathway promotes acquisition/handling (grabbing, biting) of objects, including prey (Park et al , 2018), and activation of a GABAergic projection from lateral hypothalamus to lateral/ventrolateral PAG motivates attack on prey (Li et al , 2018). In these studies, predatory behaviour was induced in the presence of prey/prey-like stimuli, suggesting these pathways serve to motivate, rather than command, hunting.…”
Section: Discussionmentioning
confidence: 99%
“…Comoli et al (2005)]. Although electrical stimulation of brain regions, including the optic tectum, can evoke hunting actions (Ewert, 1970; Bels et al , 2012) and recent studies in rodents have identified circuits that motivate predatory behaviour (Han et al , 2017; Li et al , 2018; Park et al , 2018), neurons that command vertebrate hunting have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%